Marketing and designing the tourist experience - Frochot, Isabelle; Batat, Wided (Current developments in the geographis of leisure and tourism, 2013)
The topic of 'experience' is becoming central to full understanding of consumer behaviour. The book covers the key sectors where it is critical - from resort management and tourist information to destination marketing. International in scope it backs up the theory throughout with relevant case materials, questions and exercises..